The Effect Of Quantum Reading Strategy On The Intensive Reading Ability Of 4th Grade Students Of State-Owned Elementary School No.10 Bandar Buat Padang - Azlin, Siti Nur; Sukma, Elfia; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to find out the effect of quantum reading strategy on the intensive reading ability of 4th grade students of state-owned Elementary School No.10 Bandar Buat, Padang. This study used a quantitative approach in the form of a quasi-experimental design. The research design of this study is the non-equivalent posttest-only control group design and the sampling technique is saturation sampling. based on the analysis results of the hypothesis test with the significance level of 5%, it was found that t calculation > t table (2,95995 > 1,67155). It is concluded that the quantum reading strategy has a significant effect on the intensive reading ability of 4th grade students at state-owned Elementary School No.10 Bandar Buat, Padang. Keywords: quantum reading, intensive reading, elementary school students